Marketing de contenido para la promoción del Paseo Roberto en Bahía de Caráquez: Content marketing for the promotion of the Roberto ride in Bahía de Caráquez - Solórzano Palma, Liceth Estefanía (2023)
Promotion has become the most effective strategy within Content Marketing for the promotion of tourist attractions and resources. Currently, marketing is a fundamental contribution to provide information through digital platforms as well as traditional media. The objective of the study was to analyze the content marketing strategy to promote the tourist attraction located in the city of Bahía de Caráquez "Paseo Roberto". The methodology used was of a quantitative order that allowed the study of statistical figures, as well as allowing the analysis of the current situation regarding the importance of content marketing for the promotion of a tourist attraction. A survey consisting of 10 open questions on a Likert scale was designed to develop an interpretation that contributes to the search for more effective promotional strategies. The study population were local, national, and foreign tourists who frequent the destination, selecting a non-probability sampling for convenience for a total of 100 surveyed tourists. The statistical software SPSS v. 26 to process the survey and determine the reliability of the instrument where Cronbach's alpha yielded the result of 0.856 for 28 items. Among the most representative results is that respondents prefer the social network Tik Tok to view content through Reels about promoting attractiveness. It is concluded that the instrument applied facilitated the recognition of the importance of content marketing for the promotion of the attractive "Paseo Roberto".